OBESITAS: ASPEK KLINIS, FAKTOR RISIKO, DAN DAMPAK KESEHATAN - Enriko Aprilio; Dian Isti Angraini; Putri Damayanti; Reni Zuraida (Nusantara Hasana Journal, 2026)
Obesity has emerged as one of the most significant global health concerns in recent decades, with its prevalence rising across different age groups and socioeconomic settings. Characterized by excessive accumulation of body fat, obesity disrupts metabolic regulation and substantially increases the risk of chronic diseases such as type 2 diabetes, cardiovascular disorders, liver disease, and various cancers. Recent evidence also highlights the rapid growth of obesity among children and adolescents, indicating long-term health consequences that may appear earlier in adulthood. This literature review examines the clinical aspects of obesity, including its definition, physiological mechanisms, and metabolic characteristics. It also explores the multifactorial risk factors associated with obesity, encompassing genetic predisposition, lifestyle patterns, socioeconomic conditions, and environmental influences. Furthermore, the review discusses the broad health impacts of obesity, ranging from metabolic and cardiovascular complications to psychological outcomes and intergenerational risks. The findings emphasize the need for comprehensive preventive and management strategies that integrate public health approaches, behavioral interventions, and supportive health policies to address the increasing burden of obesity at both individual and population levels.